Merajut Asa di Tanah Mutiara Hitam: Analisis Faktor Penghambat dan Strategi Peningkatan Kualitas Pendidikan di Pedalaman Papua - Sinta Evenia Simbolon; Erni Murniarti; Bintang R Simbolon (Jurnal Ilmiah Global Education, 2026)
This research analyses the inhibiting factors and formulates strategies to improve the quality of education in inland Papua, known as the “Land of the Black Pearl”. Although the region is rich in natural resources, Papua still faces significant challenges in education access and quality compared to other regions in Indonesia. Using a qualitative approach, data was collected through in-depth interviews with stakeholders, field observations and analyses of relevant documents. This research was conducted in school SD INPRES 40 Aimasi Papua Barat in May-June 2025, involving 8 teachers as participants. The results identified several key inhibiting factors, including limited infrastructure, a shortage and inequality of qualified educators, a curriculum that lacks relevance to the local context, extreme geographical challenges, and socio-cultural and economic factors of the local community. Based on these findings, the study proposes a comprehensive education quality improvement strategy. These strategies include developing adaptive infrastructure, increasing the capacity and equitable distribution of teachers, developing local wisdom-based curricula, utilising information and communication technology (ICT) for distance education, and strengthening the role of communities and local governments in supporting education. It is hoped that this research can make a real contribution to the formulation of more effective policies and intervention programmes.